Longitudinal path analysis of ecosystem water yield effects and its driving forces in the upper Yangtze River basin - Hongxiang Wang; Jiaqi Lan; Lintong Huang; Xuyang Jiao; Kaiang Zhao; Wenxian Guo (Ecological Indicators)
Water ecosystem services in the upper Yangtze River basin (UYRB) provide essential ecological and economic benefits. This study evaluated the spatiotemporal changes in water yield (WY) from 2000 to 2020 and analyzed interactions between human activities and climate factors using the InVEST-AWY and SWAT models. The raster- and sub-basin-scale simulations captured spatial heterogeneity and validated the model outputs. Future WY distribution for 2030 was projected under two socioeconomic scenarios—urban development (UD) and ecological protection (EP)—by integrating CMIP6 climate data with the PLUS model to assess the combined effects of land use and climate change. The results show a steady increase in WY between 2000 and 2020, with low WY regions shifting westward. Climate factors, particularly precipitation, emerged as the primary drivers of WY, with their influence enhanced by interactions with socioeconomic factors over time. The impact of human activities on WY weakened after 2010, reflecting the positive outcomes of ecological protection policies. However, peak WY values in 2020 indicate a lag in the effects of these strategies on water supply. The 2030 projections revealed that the UD scenario would generate higher WY but with more uneven spatial distribution, while the EP scenario would enhance water retention and yield a more balanced distribution. Future management should balance ecological conservation with development, considering regional variability and accounting for the lag effects of land use changes. Implementing dynamic feedback mechanisms will help manage uncertainties and ensure sustainable water resource management in UYRB.